Tertiary syphilis mimicking hepatic metastases of underlying primary peritoneal serous carcinoma - Shim, Hyun Jeong (Baishideng Publishing Group Co., Limited, 2010)
Tertiary syphilis, especially in cases involving visceral gummatous disease, can be confused with cancer of the solid organs. We report a case of tertiary hepatic syphilis that manifested with intrahepatic masses in a patient who had an underlying primary peritoneal serous carcinoma (PPSC). The patient was diagnosed with PPSC and achieved a complete remission of PPSC following six cycles of platinum-based chemotherapy. Two hepatic nodules developed during the follow-up period and were initially labeled as hepatic metastases from the underlying PPSC, based on radiological findings. A resection of hepatic nodules was performed for therapeutic and diagnostic purposes, because there were no other metastatic foci except in the liver. Unexpectedly, serology and histology confirmed tertiary syphilis. This rare case emphasizes the importance of including tertiary syphilis in the differential diagnosis of a space-occupying lesion, even with an existing diagnosis of underlying cancer.